2010 International Conference on Science and Social Research (CSSR 2010) 2010
DOI: 10.1109/cssr.2010.5773690
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cross-border mergers and Acquisitions (CBMAs) performance in five East Asian countries

Abstract: Ahstract-This study aims to investigate the determinants that caused the variations in the post-CBMA performance of the target firms in the five East Asian countries, namely Malaysia, Thailand, Indonesia, the Philippines and South Korea. Using a sample from 1998 to 2004, the ownership and target firms' characteristics are examined. A four-step hierarchical analysis was used with EFCFS (Excess free cash flow per share) as a dependent variable for the post CBMA performance and independent variables including cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Consistent with previous argument, strict regulatory environment such as complicated and lengthy administration process involving various regulatory bodies (Song et al, 2010b), financial restriction on capital outflow from a home country (Jongwanich et al, 2013) and high corporate tax rate (Nagano, 2013) hampered CBMAs. Martynova and Renneboog (2008) claimed that the governance environment of a country is an important stimuli of CBMAs.…”
Section: Country-specific Factorsmentioning
confidence: 50%
See 4 more Smart Citations
“…Consistent with previous argument, strict regulatory environment such as complicated and lengthy administration process involving various regulatory bodies (Song et al, 2010b), financial restriction on capital outflow from a home country (Jongwanich et al, 2013) and high corporate tax rate (Nagano, 2013) hampered CBMAs. Martynova and Renneboog (2008) claimed that the governance environment of a country is an important stimuli of CBMAs.…”
Section: Country-specific Factorsmentioning
confidence: 50%
“…A few studies found no significant relationship between the size and abnormal return (Bhagat et al, 2011;Cakici et al, 1996;Corhay & Rad, 2000). However, others found a positive relationship between size and cumulative abnormal return of shareholders (Basuil, 2011;Du & Boateng, 2015;Song et al, 2010a). In contrast, Martynova and Renneboog (2008) found a negative effect of firm's size on the bidder's returns.…”
Section: Firm-specific Factorsmentioning
confidence: 81%
See 3 more Smart Citations